Microservices in action - Bruce, Morgan; Pereira, Paulo A. (Shelter Island, NY : Manning Publications Co., 2019)
"Microservices in Action is a practical book about building and deploying microservice-based applications. Written for developers and architects with a solid grasp of service-oriented development, it tackles the challenge of putting microservices into production. Invest your time in designing great applications, improving infrastructure, and making the most out of your dev teams. Microservices are easier to write, scale, and maintain than traditional enterprise applications because they're built as a system of independent components. Master a few important new patterns and processes, and you'll be ready to develop, deploy, and run production-quality microservices. Microservices in Action teaches you how to write and maintain microservice-based applications. Created with day-to-day development in mind, this informative guide immerses you in real-world use cases from design to deployment. You'll discover how microservices enable an efficient continuous delivery pipeline, and explore examples using Kubernetes, Docker, and Google Container Engine."--Amazon.com.
Part 1. The lay of the land. Designing and running microservices -- Microservices at SimpleBank -- Part 2. Design. Architecture of a microservice application -- Designing new features -- Transactions and queries in microservices -- Designing reliable services -- Building a reusable microservice framework -- Part 3. Deployment. Deploying microservices -- Deployment with containers and schedulers -- Building a delivery pipeline for microservices -- Part 4. Observability and ownership. Building a monitoring system -- Using logs and traces to understand behavior -- Building microservice teams.
Includes index.
CSE
Karim International
Keywords: Application software -- Development; Web applications; Service-oriented architecture (Computer science).; Electronic data processing -- Distributed processing -- Management; Computer networks -- Management; Computer science; Application software -- Development; Computer networks -- Management; Electronic data processing -- Distributed processing -- Management; Service-oriented architecture (Computer science); Web applications